Comparison of optimal oriented façade integrated solar cooling systems in Australian climate zones. (1st March 2020) - Wu, Dan; Aye, Lu; Yuan, Yanping; Mendis, Priyan; Ngo, Tuan
Highlights: Four façade integrated solar cooling systems have been investigated. The systems apply façade integrated either solar electric (PVs) or solar thermal collectors. The optimum façade orientations and system sizing have been determined. Their technical and financial performance parameters have been compared. Solar fraction and unit cooling cost are the performance parameters compared. Abstract: Solar cooling technologies have been proven to have great potential for energy saving during cooling season. Meanwhile, glass has become one of the primary structural materials used in building construction since the middle of the 20th century. Although common glass adds to the aesthetic appeal of a building, it has serious drawbacks, such as creating heat traps, preventing natural ventilation and causing glare. Highly glazed façades would cause unwanted heat transmission from the ambient, which must be extracted to outside using an air-conditioning system. Internal heat resulting from façade configurations can be responsible for up to 45% of a building's cooling requirements. A façade integrated solar cooling system can simultaneously improve building's energy efficiency, utilise solar energy and still maintain a high level of architectural and aesthetic quality. This investigation presents a consistent approach for optimising and comparing façade integrated solar cooling systems in terms of technical and financial performance. Four systems (a vapour compression cycle (VCC) chiller driven by semi-transparent photovoltaics (STPV) arrays, a single-stage absorption chiller, an adsorption chiller and a vapour compression chiller coupled with organic Rankine cycle (ORC) driven by evacuated tube solar collectors) were assessed and compared with a conventional electric vapour compression chiller. The systems investigated were modelled in TRNSYS and the models were applied to predict performance parameters in various climate zones (seven cities) in Australia. The solar fraction (SF) and unit cooling cost (UCC) were the two parameters applied to quantify the technical and financial aspects of each solar cooling system in seven cities in Australia. It was found that among the systems investigated, the VCC chiller with STPV system has the highest SF (100% except in Darwin) and lowest UCC ($0.21 kWhr −1 ) for all seven cities in Australia. In general, due to the grid as a virtual storage, ORC-VCC system has higher SF (40% and 50%) and lower UCC (5% and 10%) compared with adsorption and absorption chiller respectively in subtropical and temperate climate zones.